Determinants of timing and amplitude in the plant general stress response. Issue 2 (19th August 2015) - Bjornson, Marta; Dandekar, Abhaya; Dehesh, Katayoon
Abstract: Plants have evolved intricate signaling cascades to rapidly and effectively respond to biotic and abiotic challenges. The precise timing of these responses enables optimal resource reallocation to maintain the balance between stress adaptation and growth. Thus, an in‐depth understanding of the immediate and long‐term mechanisms regulating resource allocation is critical in deciphering how plants withstand environmental challenges. To date however, understanding of this tradeoff has focused on the amplitude of long‐term responses, rather than the timing of rapid stress responses. This review presents current knowledge on kinetics of secondary messengers involved in regulation of rapid and general stress responses, followed by rapid stress responsive transduction machinery, and finally the transcriptional response of a functional general stress responsive cis ‐element. Within this context we discuss the role of timing of initial peak activation and later oscillating peak responses, and explore hormonal and stress signaling crosstalk confounding greater understanding of these cascades. Abstract : The general stress response enables stress‐acclimation via rapid and transient reprograming of gene expression. This article reviews fundamental general stress signaling/response pathways, highlights the importance of timing in staging the response, describes determinants of response peak and amplitude, and explores the role of signaling crosstalk in these processes.